Netralitas Aparatur Sipil Negara (ASN) Dalam Kebijakan Publik Dan Pemilihan Umum - TB. Soenmandjaja SD; Tri Susilowati (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
The neutrality of ASN has always been an issue and news that has received a lot of public attention, especially during the lead up to, implementation and end of elections, both presidential, legislative and regional head elections. The fact of violations of ASN neutrality cannot be denied from several cases that have occurred, such as involvement in campaign activities, using state facilities related to office duties, making decisions or actions that favor their constituents, holding activities that lead to bias towards candidate pairs participating in the General Election (PEMILU), and so forth. This research aims to examine the neutrality of state civil servants in public policy and general elections. This research uses normative research methods. The State Civil Service Commission explains that neutrality is a very important principle to be implemented in efforts to create a professional ASN, so this concept is related to 4 things, including: political activities, public service delivery, policy making, and ASN management. Regulations regarding ASN are regulated in Article 2 letter f, Article 5 paragraph (2) letter h, Article 9 paragraph (2) Law no. 5 of 2014 concerning State Civil Apparatus, "ASN employees must be free from the influence and intervention of all groups and political parties.